Birds - Bailey, Jill; Burnie, David (New York Dorling Kindersley, 1992)
Describes the physical characteristics, habitats, and behavior of birds and examines kinds of seashore birds, woodland birds, birds of prey, and others
Includes index
scence ( Birds)
1
Keywords: Birds -- Juvenile literature; Birds -- Identification -- Juvenile literature; Birds